Refugee rights and realities : evolving international concepts and regimes - Nicholson, Frances; Twomey, Patrick M. (Cambridge University Press, 1999)
This collection examines the evolving refugee definition, the contrast of the rights of refugees as set out in international law with the often contrasting realities of state practice. It also assesses the role of UNHCR, states and the EU in developing the evolving international refugee regime.